Work Culture and Service Quality in Providing Tourist Satisfaction - Aldri Frinaldi; Muhamad Ali Embi; Lidya Ryan Utarie; Aziza Bila; Nora Eka Putri; Boni Saputra (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2022)
Tourism activities are a combination of tourism products and services that provide a tourist experience. In tourism, transportation is essential because it is one aspect that determines interest in tourism. Exciting traveling experience will give satisfaction to tourism. Work culture and service quality are also determinants of tourist satisfaction. This study aims to indicate the influence of work culture and service quality in providing tourism satisfaction. Its influence is seen partially and simultaneously. Locus of this research at public transportation in the tourism area of Bukittingi. This research uses a quantitative approach. Data were taken from 300 respondents who have been selected using Slovin Formula. Data already obtained with a questionnaire that is valid and reliable. The result of the research showed that work culture and service quality partially and simultaneously influenced customer satisfaction.